Developing the Method for Estimating the Costs of Providing Broadband Universal Service: Korean Case - Hyeongjik Lee; Seonkoo Jeong; Kwanghee Lee (International Telecommunications Society (ITS), 2020)
While the importance of both broadband itself and its speed increases in a whole society, the high cost of providing broadband as universal service at high speed still raises a question of whether to introduce the USO. Therefore, the introduction of broadband universal service at 100Mbps since 2020 in Korea could be a meaningful case to study the necessity of broadband USO. This study attempts to propose an estimation model of the costs of providing broadband universal service in Korea and to introduce how the results by utilizing method can contribute to understanding the Korean case. In particular, since the proposed model was developed based on the bottom up (BU) approach, which establish es an efficient network using the latest technologies, this paper suggested the accurate and reliable cost of providing broadband universal service with nationwide coverage in Korea by the estimation model. The main findings are twofold. First, the total cost of providing broadband USO at 100Mbps through FTTH technology was at 1.34 trillion. Since it was relatively small compared with the results in similar previous studies, the introduction of broadband universal service was reasonably acceptable in Korea. Second, there was no significant difference in the average cost per building for broadband USO between 50Mbps and 100Mbps; thus the Korean government's decision, which sets the broadband speed for broadband USO at 100Mbps, was sufficiently reasonable at least from a cost perspective. Those results imply that at least developed cou ntries with relatively high broadband penetration could consider providing broadband universal services at least 50Mbps by fiber based technologies. They also suggest that the technology neutral approach could contribute to the cost effective deployment of broadband for USO.
Keywords: 330; cost estimation; universal service; broadband; Korea